Assessment and prevention of tooth decay in children - AlDomyati, Roaa Mohammad; Alhawaj, Zainab Mohammed; Bin Surayhid, Ibrahim Khalid; Rafiq, Samiah Adnan; AL Saffar, Noor Shaker; Ali Almatrudi, Abdullah; Almousa, Fatimah Mohammad; Al Nemer, Kholoud Abdullah; Aldhafer, Abdulelah Abdullah; Alsaywed, Rafal Abdulrahman; Alharthi, Ali Salem (International Journal Of Community Medicine And Public Health, 2022)
It has been solidified by science that dental decay is transmittable. Despite improvements in other age groups, there is indication that dental decay in young children is on the rise. There has not been an improvement in practice as a result of risk assessment research. Although definite trials are required, antiseptics, chlorhexidine varnish, and polyvinylpyrrolidone iodine (PVI-I) may be useful. Despite not being extensively distributed to the most vulnerable, fluorides continue to be the most beneficial interventions. Although conclusive trials have not been carried out, fluoride varnish is a fairly efficient topical preventative for young children. The promise of silver diamine fluoride must be studied in the US. Xylitol is safe and reliable, according to the data, although it is not widely used. Despite numerous studies, wide adoption of dental sealants has not taken place, despite being a fundamental component of public policy. We draw the conclusion that while research has demonstrated the negative public health impact of tooth decay, not enough of it has been conducted to address the growing incidence of pediatric dental disease globally. Technology must be translated from studies to practice in order to stop childhood teeth decay. This should include conducting translational studies and putting the latest technological and scientific developments into use.